2011
DOI: 10.1158/1078-0432.ccr-11-1570
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Differences between Colon and Rectum Tumors

Abstract: Purpose: Colorectal cancer studies typically include both colon and rectum tumors as a common entity, though this assumption is controversial and only minor differences have been reported at the molecular and epidemiologic level. We conducted a molecular study based on gene expression data of tumors from colon and rectum to assess the degree of similarity between these cancer sites at transcriptomic level.Experimental Design: A pooled analysis of 460 colon tumors and 100 rectum tumors from four data sets belon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
47
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 41 publications
6
47
0
1
Order By: Relevance
“…This is consistent with clinical practice, where colon and rectal cancers are treated as distinct entities (47), and a growing body of evidence that associations between dietary patterns, chemoprotective nonsteroidal anti-inflammatory drugs (NSAIDs), and CRC risk differ across anatomic subsites (21,37). In contrast, a recent comprehensive molecular characterization of human colon and rectal cancer demonstrated that after excluding hypermutated cancers, colon and rectal cancers appear to have similar patterns of genomic alteration (40).…”
supporting
confidence: 73%
See 2 more Smart Citations
“…This is consistent with clinical practice, where colon and rectal cancers are treated as distinct entities (47), and a growing body of evidence that associations between dietary patterns, chemoprotective nonsteroidal anti-inflammatory drugs (NSAIDs), and CRC risk differ across anatomic subsites (21,37). In contrast, a recent comprehensive molecular characterization of human colon and rectal cancer demonstrated that after excluding hypermutated cancers, colon and rectal cancers appear to have similar patterns of genomic alteration (40).…”
supporting
confidence: 73%
“…Of the top 20, five were HOX genes (HOXA3, HOXD9, HOXD10, HOXD11, and HOXD-AS2, a HOXD cluster anti- sense RNA) with all but HOXA3 expressed at higher levels in sigmoid colon. This is noteworthy, because several HOX genes have been associated with tumor location (47). In addition, HOX overexpression contributes to stem cell overpopulation that drives colon tumorigenesis (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that colon and rectal cancer were similar but different types of cancer (14,16,24,26). Therefore, we continued our study by analyzing colon and rectal cancer as matched pairs (Table IV and Fig.…”
Section: Differential Expression Of Serum Ca19-9 Levels Between Colonmentioning
confidence: 98%
“…The CIN pathway is far more common in rectal compared to colon cancers (24,25). In addition, several homeobox genes were found to be associated with tumor location (26). A different number of mutations induce varying mechanisms of oncogenesis in colon and rectal cancer.…”
mentioning
confidence: 99%